2016
DOI: 10.1007/s00127-016-1292-6
|View full text |Cite
|
Sign up to set email alerts
|

Veterans are not the only ones suffering from posttraumatic stress symptoms: what do we know about dependents’ secondary traumatic stress?

Abstract: PurposePrevious research has mainly focused on veterans’ mental health problems, especially on posttraumatic stress disorder (PTSD). Less is known about the impact that the veteran’s experienced potentially traumatic events (PTEs) might have on their significant others. Therefore, we reviewed the scientific literature to find out what is known about the prevalence of secondary traumatic stress (STS) in significant others of veterans.MethodsWe systematically searched Pubmed, PsycINFO, Embase, Cochrane Library a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
0
35
1
Order By: Relevance
“…Such information has important clinical implications and some studies have argued for symmetry in the specific health problems of service members and their spouses. For instance, research has explored the relationship between combat-related PTSD and a type of secondary traumatic stress disorder experienced by spouses (Diehle, Brooks, & Greenberg, 2017). The evidence on this precise linkage is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such information has important clinical implications and some studies have argued for symmetry in the specific health problems of service members and their spouses. For instance, research has explored the relationship between combat-related PTSD and a type of secondary traumatic stress disorder experienced by spouses (Diehle, Brooks, & Greenberg, 2017). The evidence on this precise linkage is limited.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence on this precise linkage is limited. Research has shown that the PTSD of one spouse results only in general psychological distress in the other, if not PTSD-specific symptoms (Diehle, et al, 2017). Furthermore, research finds that fewer than 20% of those married to someone with PTSD attribute their own distress specifically to their spouse's military experience (Renshaw et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that spouses and children of service personnel/veterans with PTSD can experience significant mental health difficulties, including secondary PTSD symptoms and emotional dysregulation problems, as a consequence. 13 The provision of psychoeducation to families, an assessment of families' own needs, as well as practical and emotional support, may be beneficial to support familial coping. Military-affiliated charities, such as the Royal British Legion, Help for Heroes or Combat Stress, may be particularly well placed to provide military-connected families with targeted advice and support.…”
Section: Role Of Healthcare Professionalsmentioning
confidence: 99%
“…A recent review of secondary traumatic stress within the families of veterans concluded that there was little evidence that the parents or children are increased risk but that the same could not be said for partners 21. There is a growing body of work demonstrating that the partners of help-seeking veterans are themselves reporting a high burden of mental health difficulties 22–25…”
Section: Presentations Of Help-seeking Veteransmentioning
confidence: 99%